Moral Character: Challenges for Auditors in Serving Public Interest - Sasongko Budisusetyo (Journal of Economics, Business, and Accountancy Ventura, 2018)
The purpose of this research is to examine how auditorsâ€™ moral character influences their ethical decision making when faced with an ethical dilemma situation. Organizational ethical climate and the intensity of competition in a public accounting firm are used as a moderating variable. The results of this study have implications as ethical decision quality can be obtained and carried through increased moral character. By identifying the potential drivers for improving auditorsâ€™ moral character, this research can inform the discussions and strategies of professional bodies, regulators and government on improving the audit quality of financial reports. The intensity of competition in a public accounting firm may have an impact on improving the quality of auditing services, but on the other hand, also have an impact on ethical issues. This research lays the foundation for competition among public accounting firms being recognized as a major issue in industrial policy in auditing services.Â